Entrepreneurial orientation as an antecedent to the rapid internationalization of Moroccan SMEs in the women’s entrepreneurship field - Rouijel, Mohamed Reda (Business, Management and Economics Engineering, 2024)
Purpose – This article aims to explore the importance of the international entrepreneurial orientation (IOE) of Moroccan women entrepreneurs (based on innovation, risk-taking and proactivity) in the speed of internationalization of Moroccan SMEs through the niche strategy as an intermediate variable.Research methodology – We adopted a quantitative study on a sample of 45 Moroccan SMEs to test the research hypotheses using the structural equation method, under Smart-PLS software.Findings – A significant relationship between the international entrepreneurial orientation of Moroccan women entrepreneurs and the speed of internationalization with the intermediation of the niche strategy. Despite well-calculated steps, innovative products and the courage to take risks on foreign markets, women entrepreneurs tend to adopt niche strategies to be more protected in the internationalization process: both to avoid direct competition from large companies and to speed up the internationalization process Research.Limitations – Theoretically, it was difficult to operationalize the phenomenon studied, for several reasons: the large number of movements in this approach, the number of variables mobilized. Methodologically, the criteria used to select the sample made it difficult to find more than 45 eligible companies (Exploratory quantitative study).Originality/Value – This article is one of the very few to combine international and women’s entrepreneurship. Furthermore, this is the first article in the field of women’s international entrepreneurship, as far as I know, that addresses the relationship between entrepreneurial orientation and the speed of internationalization of exporting SMEs.